2022
DOI: 10.1021/jacs.2c11210
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photodissociation Reveals the Molecular Mechanism of Crown Ether Microsolvation Effect on the Gas-Phase Native-like Protein Structure

Abstract: Maintaining the protein high-order structures and interactions during the transition from aqueous solution to gas phase is essential to the structural analysis of native mass spectrometry (nMS). Herein, we systematically interrogate the effects of charge state and crown ether (CE) complexation on the gas-phase native-like protein structure by integrating nMS with 193 nm ultraviolet photodissociation (UVPD). The alterations of photofragmentation yields of protein residues and the charge site distribution of fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The mass spectrometer was equipped with a 193 nm ArF excimer laser (EX5AIN/500-465, GAM LASER INC, USA) for UVPD had been reported in our previous studies. However, due to the long polymer chain being difficult to resolve on MS, we set the source-induced dissociation of 100 V to generate a short chain before UVPD in analysis of MNP polymers. Then, the MNP precursor ions with specific polymerization degrees were isolated into the MS dissociation cell and irradiated with a 193 nm laser (1.5 mJ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometer was equipped with a 193 nm ArF excimer laser (EX5AIN/500-465, GAM LASER INC, USA) for UVPD had been reported in our previous studies. However, due to the long polymer chain being difficult to resolve on MS, we set the source-induced dissociation of 100 V to generate a short chain before UVPD in analysis of MNP polymers. Then, the MNP precursor ions with specific polymerization degrees were isolated into the MS dissociation cell and irradiated with a 193 nm laser (1.5 mJ).…”
Section: Methodsmentioning
confidence: 99%
“…It is well-known the most powerful MS strategy for the molecular structure elucidation of biopolymers is tandem MS (MS/MS) by dissociating the precursor ions into fragment ions containing both sequence and structure information . Ultraviolet photodissociation (UVPD) is an emerging MS/MS strategy in recent years by using the pulsed UV laser to excite the molecular backbone and induce efficient overall dissociation. UVPD with 193 nm ArF laser can produce rich types of fragment ions, which have been widely applied for the sequence and structure characterization of biopolymers including proteins, glycans, and lipids. …”
Section: Introductionmentioning
confidence: 99%
“…33,34,57,61,63,64,67,68 In addition, IMS−MS and ultraviolet photodissociation (UVPD) MS experiments have indicated that complexation of proteins with 18C6 favors the retention of native-like structure upon transfer to vacuum. 32,33,69 IMS−MS has also been combined with tandem mass spectrometry experiments to elucidate the contribution of protonated lysine residues to the structural rearrangement of ubiquitin during the ESI process. 70 Although complexation with 18C6 has proven a valuable tool for the analysis of isolated biomolecular cations, no equivalent ligand has been developed for complexation with anionic functional groups such as carboxylate moieties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, for biomolecules that adopt a well-defined conformation in solution, complexation occurs preferentially at solvent-accessible sites, yielding a correlation between the condensed-phase structure and number of complexed 18C6 molecules. This relationship has been leveraged in selective noncovalent adduct protein probing (SNAPP) to quantify the influence of solvent conditions or primary sequence on protein structure. ,,,,,,, In addition, IMS–MS and ultraviolet photodissociation (UVPD) MS experiments have indicated that complexation of proteins with 18C6 favors the retention of native-like structure upon transfer to vacuum. ,, IMS–MS has also been combined with tandem mass spectrometry experiments to elucidate the contribution of protonated lysine residues to the structural rearrangement of ubiquitin during the ESI process …”
Section: Introductionmentioning
confidence: 99%
“…Photochemistry, which involves the use of light for chemical reactions, , holds significant value for a wide range of practical applications, including drug development, solar energy conversion, photodynamic therapy, and photovoltaic materials . To effectively utilize photochemical reactions, it is crucial to explore, comprehend, and control these reactions on ultrafast time scales, specifically involving the breaking and forming of chemical bonds. , Achieving selective excitation of molecular dissociation reactions has long been a goal in this field. Typically, the dissociation process involves the transient complex transition to an excited electronic state with a purely repulsive potential. This transition occurs rapidly within fewer than one vibrational period.…”
mentioning
confidence: 99%